Systemic lupus erythematosus complicated by portal vein thrombosis: A case report - Syed Jamil Abdal, Syed; Shahin, Md Abu; Islam, Md Ariful (Bangladesh Medical Journal, 2024)
A 24-year-old female got admitted in a remote hospital with one and half month previous history of gradually increasing swelling of the abdomen followed by swelling of the both legs and face without any discernable etiology. Later she is diagnosed as a case systemic lupus erythematosus (SLE) based on clinical features and serology. She had neither any history of having pro-thrombotic risk factor nor any history of deep vein thrombosis. Her Anti-β2 Glycoprotein 1 (Ab IgM & IgG) was marginally positive. Her ultra-sonogram of abdomen showed moderate ascites, gross thrombosis & stenosis in portal system (main trunk of portal vein, both proximal branches of portal vein, splenic vein at pancreatic area, superior mesenteric vein at confluence) that were 100% blocked that also supported by CT scan of abdomen and Doppler ultra-sonogram. Her Doppler ultra-sonogram of lower limbs were normal. She was treated initially with albumin infusion, enoxaparin, warfarin, aspirin, hydroxychloroquine and medium dose prednisolone. Bangladesh Med J. 2023 Sept; 52(3): 47-51